HUBUNGAN PEER GROUPSUPPORT DENGAN PERILAKU MEMILIH JAJANAN SEHAT PADA ANAK USIA SEKOLAH DI MADRASAH IBTIDAIYAH (MI) ALMUKMIN PRAWOTO KOTA PATI - Menik Kustriyani; Tri Sakti Widyaningsih; Adi Prasetyo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background : The culture of having snack is a part of daily life for people of almost all ages, especially for children of school age. Many of them buy snack based on their preference without considering the ingredients included in that snack. This will give a bad impact for their health because they do not really know how to choose healthy snack at school. One of the factors which can influence them in choosing snack is the peer group support. The objective of this research is to find out the relationship between the peer group support and the behaviour to choose healthy snack on school age children at Madrasah Ibtidaiyah (MI) Almukmin Prawoto Pati Regency.Method : This study used cross sectional correlative descriptive method. There are 40 students of fifth grade of MI Almukmin to be the respondent using total sampling. The data were analyzed statistically by using non parametric test called rank spearman. Result : It shows that the correlation of coefficient score is p = 0.472 p value = 0.0002(<0.05) so that Ho is rejected and Ha is accepted, it means that there is a relationship between the peer group support and the behaviour to choose healthy snack.Conclusion : It is concluded that there is a relationship between the peer group support and the behaviour to choose healthy snack.Suggestion : Based on this research, it is suggested that this research can be used for the correction and the utilization of the research about the relationship between the peer group support and the behaviour to choose healthy snack on school age children.Key words : Peer group support, the behaviour to choose healthy snack